Oil-suspended particulate material aggregates as a tool in preventing potential ecotoxicological impacts in the São Paulo river, Todos os Santos Bay, Bahia, Brazil: Influence of salinity and suspended particulate material. Issue 1 (15th November 2016) - Miranda, Lorena S.; Moreira, Ícaro T.A.; Oliveira, Olívia M.C.; Santos, Carlito P.; Pinheiro, Samires M.M.; Oliveira, Lua M.L.; Martins, Adriele B.O.; Filho, Milton S.C.
Abstract: Recent studies have revealed the occurrence of a natural process of interaction between oil droplets and suspended particulate material, resulting in the formation of aggregates which are dispersed in the water column, known as oil-suspended particulate material aggregates (OSAs). The experiments aimed to investigate the contribution of OSAS in indicating where most likely is the oil sedimentation in the São Paulo river, Todos os Santos Bay, Brazil, in order to predict possible ecotoxicological risks caused by oil spills. The results showed that salinity and MPS concentration interfere on the formation of aggregates. In addition, the point 3 was nominated as the most vulnerable area to the potential ecotoxicological impacts of oil spills and should be treated as a priority area for the application of preventive and mitigating techniques.